A representation learning approach for recovering scatter‐corrected spectra from Fourier‐transform infrared spectra of tissue samples. Issue 3 (27th December 2020) - Raulf, Arne P.; Butke, Joshua; Menzen, Lukas; Küpper, Claus; Großerueschkamp, Frederik; Gerwert, Klaus; Mosig, Axel
Abstract: Infrared spectra obtained from cell or tissue specimen have commonly been observed to involve a significant degree of scattering effects, often Mie scattering, which probably overshadows biochemically relevant spectral information by a nonlinear, nonadditive spectral component in Fourier transform infrared (FTIR) spectroscopic measurements. Correspondingly, many successful machine learning approaches for FTIR spectra have relied on preprocessing procedures that computationally remove the scattering components from an infrared spectrum. We propose an approach to approximate this complex preprocessing function using deep neural networks. As we demonstrate, the resulting model is not just several orders of magnitudes faster, which is important for real‐time clinical applications, but also generalizes strongly across different tissue types. Using Bayesian machine learning approaches, our approach unveils model uncertainty that coincides with a band shift in the amide I region that occurs when scattering is removed computationally based on an established physical model. Furthermore, our proposed method overcomes the trade‐off between computation time and the corrected spectrum being biased towards an artificial reference spectrum. Abstract : Practical application of Fourier transform infrared microscopy commonly involves substantial preprocessing of the underlying infrared spectra, where one commonly used procedure removes spectral components that are due to scattering. Using Bayesian neural network approaches, we unveil uncertainties in the neural network approximation that coincide with crucial band shifts that occur in the scattering corrected spectra.